Combined effect of game position and body size on network-based centrality measures performed by young soccer players in small-sided games - Borges, Paulo Henrique; da Costa, Julio Cesar; Ramos-Silva, Luiz Fernando; Praça, Gibson Moreira; Ronque, Enio Ricardo Vaz (Frontiers in Psychology, 2022)
This study verified the effects of body size and game position on interactions performed by young soccer players in small-sided games (SSG). The sample consisted of 81 Brazilian soccer players (14.4±1.1 years of age). Height, body mass, and trunk-cephalic height were measured. SSG was applied in the GK3-3GK format, and Social Network Analyses were carried out through filming the games to obtain the following prominence indicators: degree centrality, closeness centrality, degree prestige, and proximity prestige, in addition to network intensity and number of goals scored. Factorial ANOVA was used to test the effects of game position, body size, and respective interaction on centrality measurements (p<0.05). Similarity between game positions in body size indicators (p>0.05), and significant effect of body size on number of goals scored were observed (p=0.04, Ƞ2=0.04). The game position affected degree centrality (p=0.01, Ƞ2=0.79), closeness centrality (p=0.01, Ƞ2=0.90), and network intensity (p=0.02, Ƞ2=0.80), in which midfielders presented the highest network prominence values when compared to defenders and forwards. In conclusion, midfielders are players with high interaction patterns in the main offensive plays, which behavior is independent of body size.